2016
DOI: 10.1371/journal.pone.0165501
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Autoantigens Targeted by Anti-Citrullinated Protein Antibodies In Vivo: Prominent Role for Epitopes Derived from Histone 4 Proteins

Abstract: Anti-citrullinated protein antibodies (ACPA) have become an integral part of the clinical definition of rheumatoid arthritis, and are hypothesized to be important in the immunopathogenesis of this autoimmune disease. Several citrullinated proteins have been demonstrated to serve as candidate autoantigens for the ACPA, based on in vitro immune reactions between citrullinated peptides/proteins and RA sera. Yet it remains unclear whether the autoantigens identified in vitro are indeed directly and specifically ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Nine citrullinated peptides were identified, all of which were only detected in EVs from RA joints with high‐level inflammation (Table 2). These included citrullinated peptides derived from fibrinogen alpha (FGA), actin [β‐actin (ACTB)/ACTG] and histone H3, which are known to be recognised by anti‐citrullinated peptide antibodies (ACPA) 14–16 . Consistent with this, the majority of patients, in whom citrullinated EV peptides were observed, were ACPA‐positive.…”
Section: Resultsmentioning
confidence: 75%
“…Nine citrullinated peptides were identified, all of which were only detected in EVs from RA joints with high‐level inflammation (Table 2). These included citrullinated peptides derived from fibrinogen alpha (FGA), actin [β‐actin (ACTB)/ACTG] and histone H3, which are known to be recognised by anti‐citrullinated peptide antibodies (ACPA) 14–16 . Consistent with this, the majority of patients, in whom citrullinated EV peptides were observed, were ACPA‐positive.…”
Section: Resultsmentioning
confidence: 75%
“…In the available samples tested, the calculated ACPA score correlated with anti‐CCP titers (r = 0.55, P = 0.01; n = 214). ACPA levels directed toward an immunodominant citrullinated epitope derived from the histone 4 protein showed a high degree of correlation between the levels of anti–Cit‐H4 antibodies and the ACPA score in sequential samples from the progressors (r = 0.66, P = 0.0001; n = 42).…”
Section: Resultsmentioning
confidence: 98%
“…Levels of ACPA targeting the specific peptide Cit‐H4 were closely correlated with increasing ACPA scores, indicating a relationship between these 2 events. We have previously shown that this peptide is an immunodominant autoantigen in RA synovial fluid, where ongoing NETosis may fuel the autoimmune response . These findings suggest that the autoimmune response to Cit‐H4 likely develops outside the joint as part of a broader ACPA response, and then becomes amplified in the inflammatory synovial microenvironment.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…PAD2 and PAD4 are expressed in RA synovium and their presence correlates with inflammatory markers [ 11 13 ]. Among the best described PAD substrates is fibrinogen, which is present in the synovium of RA patients [ 14 18 ] together with numerous other citrullinated self-antigens including vimentin, alpha-enolase (ENO1), collagen type II and histones, all of which have proposed pathogenic relevance [ 19 24 ]. PAD2 seems less restricted by the amino acid composition surrounding the acceptor arginine residue than PAD4 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%